2020
DOI: 10.1186/s12967-020-02606-3
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for elderly patients with squamous non-small cell lung cancer: a population-based study

Abstract: Background Squamous cell carcinoma (SCC) is a main pathological type of non-small cell lung cancer. It is common among elderly patients with poor prognosis. We aimed to establish an accurate nomogram to predict survival for elderly patients (≥ 60 years old) with SCC based on the Surveillance, Epidemiology, and End Results (SEER) database. Methods The gerontal patients diagnosed with SCC from 2010 to 2015 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. The independent progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…The previous studies reported that patients with NSCLC diagnosed at the age over 80 years contributed to worse LCSS and OS, 26 , 27 which were consist with our investigation. Worse nutritional status, reduced physiological reserve, basic diseases and poor tolerance to cancer treatment in the older group might be explanations.…”
Section: Discussionsupporting
confidence: 92%
“…The previous studies reported that patients with NSCLC diagnosed at the age over 80 years contributed to worse LCSS and OS, 26 , 27 which were consist with our investigation. Worse nutritional status, reduced physiological reserve, basic diseases and poor tolerance to cancer treatment in the older group might be explanations.…”
Section: Discussionsupporting
confidence: 92%
“…The differences in these results may indicate marriage is not a direct influence on tumor prognosis, which could result from several factors, such as sociodemographic differences in culture and economy between regions. Chen et al also noted that the current studies only recorded marital status at the time of diagnosis and did not record information on changes in marital status after diagnosis, which could lead to biased results (113). On the other hand, the present data used in most relevant studies we reviewed are from 10 years ago, and the data source is relatively single.…”
Section: Marital Statusmentioning
confidence: 86%
“…A prognostic model of squamous cell carcinoma in the elderly (115,116). Overall, unmarried patients have worse overall survival than those who had been married (married or divorced) (112)(113)(114)(115)(116)(117)(118). The differences in these results may indicate marriage is not a direct influence on tumor prognosis, which could result from several factors, such as sociodemographic differences in culture and economy between regions.…”
Section: Marital Statusmentioning
confidence: 99%
“…Assuming that ILA is a precursor to IPF, fibrosis inherent in ILA may have influenced tumor arousal, thus resulting in higher cancer staging and larger tumor size. Squamous cell carcinoma is associated with an adverse prognosis compared with adenocarcinoma 26 . Tumor staging reflects patient outcomes, that is, a higher staging is associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma is associated with an adverse prognosis compared with adenocarcinoma. 26 Tumor staging reflects patient outcomes, that is, a higher staging is associated with a worse prognosis. The current study revealed that the presence of ILA is significantly associated with squamous cell carcinoma and higher cancer staging.…”
Section: Discussionmentioning
confidence: 99%